2001
DOI: 10.1002/pdi.163
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐conceptual folic acid supplementation in type 1 diabetes

Abstract: Aim To document peri‐conceptual folic acid supplementation in women with type 1 diabetes mellitus (DM) attending the diabetic ante‐natal clinic of a university teaching hospital. Methods Women with pre‐existing type 1 DM who booked at the diabetes antenatal clinic at University Hospital, Nottingham over 3 years (1996–98) took part in a telephone survey about folic acid supplements. Results Data was available on 50 women, 65 pregnancies. Folic acid supplements were used before 50.7% (33) pregnancies, all planne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Details regarding study aims, participant characteristics, methods, and main findings are available in Appendix Table 4. In the 303 studies, 2,618,066 participants took part, with a minimum sample size of 50 (a UK-based study with women with diabetes) (Wills and Page, 2001) and maximum of 424,065 (a study of 30 sub-Saharan African nations) (Amo-Adjei and Anamaale Tuoyire, 2016). Two hundred and five studies were conducted in developed nations, 96 in developing nations, one study combined 32 low-income countries (Guliani et al, 2014), and in one study the country could not be identified (DeLuca and Lobel, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Details regarding study aims, participant characteristics, methods, and main findings are available in Appendix Table 4. In the 303 studies, 2,618,066 participants took part, with a minimum sample size of 50 (a UK-based study with women with diabetes) (Wills and Page, 2001) and maximum of 424,065 (a study of 30 sub-Saharan African nations) (Amo-Adjei and Anamaale Tuoyire, 2016). Two hundred and five studies were conducted in developed nations, 96 in developing nations, one study combined 32 low-income countries (Guliani et al, 2014), and in one study the country could not be identified (DeLuca and Lobel, 1995).…”
Section: Resultsmentioning
confidence: 99%